(1*4)+x=(x*3)+7

Simple and best practice solution for (1*4)+x=(x*3)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1*4)+x=(x*3)+7 equation:



(1*4)+x=(x*3)+7
We move all terms to the left:
(1*4)+x-((x*3)+7)=0
We add all the numbers together, and all the variables
x-((+x*3)+7)+4=0
We calculate terms in parentheses: -((+x*3)+7), so:
(+x*3)+7
We get rid of parentheses
x*3+7
Wy multiply elements
3x+7
Back to the equation:
-(3x+7)
We get rid of parentheses
x-3x-7+4=0
We add all the numbers together, and all the variables
-2x-3=0
We move all terms containing x to the left, all other terms to the right
-2x=3
x=3/-2
x=-1+1/2

See similar equations:

| z/5+9=-77 | | z/5+9=77 | | k/6+5=19 | | 12(x+6)=24 | | -44+5x-x=36 | | /(5x+9)(5x−9)=0 | | k/6+5=9 | | 4(x+1)=3(x+7) | | 2(2x-11)+3x=-1 | | -4u+47=5(u+5) | | 5d+3=48 | | 3.4(8a+12)=25.8 | | -7v+4(v+6)=30 | | 6d+3=45 | | 3.00=0.5b | | 18-h+4=22-6 | | h()=4 | | /2x=4 | | (x-2)^2-0.25=0 | | -10=t-7 | | 24+2x=54 | | 2.25+0.50x=3.75 | | 8x+4x+3+6=7x+3+4x | | 23+2x=43 | | (3x-2)=3(3x-2)+1 | | 3(9s+2)-12s=3(5s+5)-16 | | 2-x=3x10 | | X(x+3)(3x-4)=0 | | x-3=8x+322 | | 25-3p=17-2p | | t/3+1=-1 | | 6(2x-1)=2(6x+7) |

Equations solver categories